Kennis is macht: de veelzijdige expedities van botanicus Pieter Willem Korthals (1807–1892) - Manse, Maarten (Studium, 2013)
Knowledge is power: the versatile expeditions of botanist Pieter Willem Korthals (1807–1892)The National Herbarium in Leiden houses a fascinating archive about one of the few botanists of the Committee for Natural History of the Netherlands Indies, Pieter Willem Korthals (1807–1892). The notebooks and reports of his travels in Java, Sumatra and Borneo reveal the hybrid position of Korthals in the colonial world of the Dutch East Indies. Korthals was an experienced botanist who employed methods such as measuring, taking notes and sensual observation at various locales in the Malay Archipelago. His multi-faceted fieldwork tied into the colonial administration’s desire to acquire valuable information about the islands’ human and natural resources. In particular, after the introduction in 1830 of the Cultivation System in Java, the colonial authorities in Batavia were eager to learn more about the system’s efficiency in more remote areas. By drawing upon rich archival sources, this brief essay uses Korthals’ case to shed fresh light on the production of botanical and other knowledge in the for- mer Dutch colony in the East Indies.